Metastasi cartacee Intrecci tra neoplasia e letteratura - REKUT, OLEKSANDRA (Premio Ricerca «Città di Firenze», 2017)
Six chapters, divided into four paths, over a time span that from the 19th Century reaches the year 2000, have made it possible to give voice to canonical authors and outsiders, to prose writers and poets who investigate and confront on one of the most dramatical themes of the contemporary consciousness, that of oncological disease. A sort of oncography syllabary characterized by an extraordinary mixture of medical terminology and commonplaces, colloquial expressions and courtly loans from classical languages, foreign idioms, dialects and periphrastic language originated from 'oncologhems' used instead of the word 'cancer', as well as from synaesthesias, tropes, processes, remembrances, olfactory and visual perceptions and the inflation of interrupted works.